INVESTIGATION OF FISCAL AND BUDGETARY POLICIES BASED ON ECONOMIC THEORIES - EMILIA CAMPEANU (Challenges of the Knowledge Society)
Empirical analysis of fiscal and budgetary policies cannot be achieved without first knowing how they are viewed in the economic theories. This approach is important to indicate the position and implications of fiscal and budgetary policy tools in the economic theory considering their major differences. Therefore, the paper aims is to investigate the fiscal and budgetary policies based on economic theories such as neoclassical, Keynesian and neo-Keynesian theory in order to indicate their divergent points. Once known these approaches at the economic theory level is easier to establish the appropriate measures taking into consideration the framing of a country economy in a certain pattern. This work was supported from the European Social Fund through Sectoral Operational Programme Human Resources Development 2007-2013, project number POSDRU/89/1.5/S/59184 „Performance and excellence in postdoctoral research in Romanian economics science domain” (contract no. 0501/01.11.2010).